Assessment of the psychological impact of vaccination on COVID-19 pandemic stress among B. Sc nursing students - Sahdev Singh, Vir Vikram; Bahar, Javaid Ahmad; Sharma, Komal; Bahar, Tanveer Ahmad (International Journal Of Community Medicine And Public Health, 2021)
Background: In January 2020 the world health organisation (WHO) declared the outbreak of a new coronavirus disease, COVID-19, to be a public health emergency of international concern. WHO stated that there is a high risk of COVID-19 spreading to other countries around the world. In March 2020, WHO made the assessment that COVID-19 can be characterized as a pandemic. WHO and public health authorities around the world are acting to contain the COVID-19 outbreak. To assess the level of COVID-19 pandemic stress before and after vaccination and to find out the association of COVID-19 pandemic stress scores with selected demographic variables of B. Sc nursing students. Methods: A pre-experimental study was done on 150 Nursing students in selected various nursing colleges at Meerut. The convenience sampling technique was used. Nursing Students stress were assessed by using standardized Sheldon Cohen modified stress scale. Results: The result showed that mean score before and after vaccination of stress with SD for was (0.237) nursing students was 13.20±2.202, 6.20±1.202 and correlation of patient with COVID-19 suggesting a negative significant correlation between the stress ‘r’ value was less than table value (0.273) with df 149. At (0.05) level of significance. Conclusions: there was no significant association between level of stress and demographic variables among Nursing students. It is inferred that there is moderate to severe level of stress before and moderate to mild level of stress after vaccination.